Pertumbuhan Bayam Merah (Amaranthus tricolor L.) yang diberi Pupuk Kompos Kotoran Kambing dengan Dekomposer Trichoderma harzianum - Rahmawati, Namira Putri Juliana Rangkuti, Mukarlina (Jurnal Protobiont, 2017)
Red spinach (Amaranthus tricolor L.) is one of vegetables which contains anthocyanin. This crop has not planted widely in West Kalimantan since this area has pits land. One of planting techniques to grow this crop on pits land is by adding fertilizer. The basic compost is goat manure. To fasten the composting process, Trichoderma harzianum was added as decomposer. The study was aiming at knowing the effect of goat manure compost with T. harzianum decomposer on the red spinach growth. The study used complete randomized design with 6 treatments. ANOVA result showed that adding compost fertilizer had significant effect on 6 treatment of red spinach (A. tricolor L.), such as plant height (F5,24 = 22,734, p = 0,0001), number of leaf (F5,24 = 17,266, p = 0,0001), wet weight stem (F5,24 = 11,717, p = 0,0001), dry weight stem (F5,24 = 11,770, p = 0,0001), wet weight root (F5,24 = 5,965, p = 0,0001), and dry weight root (F5,24 = 5,196, p = 0,002).